Unfairness at Work: Well-Being and Quits - Conchita D'Ambrosio; Andrew E. Clark; Marta Barazzetta (Institute of Labor Economics (IZA), 2018)
We here consider the effect of the level of income that individuals consider to be fair for the job they do, which we take as measure of comparison income, on both subjective well-being and objective future job quitting. In six waves of German Socio-Economic Panel data, the extent to which own labour income is perceived to be unfair is significantly negatively correlated with subjective well-being, both in terms of cognitive evaluations (life and job satisfaction) and affect (the frequency of feeling happy, sad and angry). Perceived unfairness also translates into objective labour-market behaviour, with current unfair income predicting future job quits.
Keywords: D63; J28; J31; 330; fair income; subjective well-being; quits; SOEP